PENGARUH KEAKTIFAN BELAJAR SISWA TERHADAP HASIL BELAJAR PRAKTIK PEMBELAJARAN MESIN BISNIS - Gayatri, Gayatri; Sulistyarini, Sulistyarini; Sumartono, Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This studi aims to study â€œactive learning towards machine learning in class XI Marketing SMK Negeri 8 Pontianakâ€. the method used is a quantitative descriptive method with the form of a study of relationship studies. Data collection techniques used are direct communication, indirect questionnaires, interview guidelines, and documentational.the sampel in the study showed that there was a positive influence on studentâ€™ learning activeness on learning outcomes indicated by the correlation coefficient of 0.135. the coefficient of determination in this study shows the contribution of the dependent variable (X), namely the effect of student learning activeness on the dependent variable (Y), namely the learning outcomes of 0.135 or 13,5%. While the rest is influenced by other variable not explained in this study. With simple lenear regression calculation obtained equation Y = 90.426+0.21 X, which means the constant value of 90.426 if the effect of student learning activeness is zero (0), then the learning outcomes of 0.221, this mean that an increase in student learning activeness by 1 then the learning outcomes will increase y 0.221.Keywords:Student LearningÂ Activeness, Learning Outcomes